(untitled) (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Hemiatrophy of the brain is the radiological finding, in the patients with seizure and/ or mental retardation and hemiparesis, usually due to insult to developing brain in fetal and early childhood. Other imaging feature is the compensatory osseous hyperplasia. This condition, also known as Dyke-Davidoff-Masson Syndrome is a rare entity and we report two such cases. JSSN 2015; 18 (1), Page: 26-28